Analisis Peran Bank Indonesia Dalam Pengembangan Umkm Di Kancah Internasional - Syahriani, Novita; Siregar, Ashabul Jannah; Nasution, Wanhar (Universitas Labuhanbatu, 2022)
The purpose of this study is to find out what the role of Bank Indonesia is in developing MSMEs on the international stage and also explore the potential of MSMEs at the North Sumatra Creative Work event to further synergize in the future in colonizing crafts and crafts in Indonesia, especially in North Sumatra. The method used is the descriptive-qualitative method, which is carried out by interviews and direct observation at the KKSU event. The findings from this study are that KKSU is one of the events that awakens and develops MSMEs in North Sumatra, and with this KKSU, MSMEs need not be afraid anymore of introducing their production to the international scene. MSMEs at the KKSU event, whether they are assisted by Bank Indonesia or not, are still embraced, both in sales and in the development of the MSMEs themselves. The role of Bank Indonesia has influenced MSMEs in North Sumatra, and with the KKSU event, it is hoped that all MSMEs in North Sumatra will be more thorough and proficient in the realm of craftsmen to be introduced more locally and internationally.